2015
DOI: 10.1038/srep09219
|View full text |Cite
|
Sign up to set email alerts
|

Reduced MCMV Δm157 viral clearance in the absence of TSAd

Abstract: The T cell specific adapter protein (TSAd) is expressed in activated T cells and NK cells. While TSAd is beginning to emerge as a critical regulator of Lck and Itk activity in T cells, its role in NK cells has not yet been explored. Here we have examined susceptibility to virus infections in a murine model using various viral infection models. We report that TSAd-deficient mice display reduced clearance of murine cytomegalovirus (MCMV) that lack the viral MHC class I homologue m157, which is critical for Ly49H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Additionally, protein kinase A (cAMP‐dependent protein kinase) activity is required for TCR‐dependent induction of TSAd expression 180 . Another potent activator of TSAd expression is a combination of phorbol myristate acetate and ionomycin (which bypasses immunoreceptor tyrosine‐based activation motif phosphorylation), both in T cells and NK cells 181 …”
Section: Tsad—an Adaptor With An Ambiguous Role In Cellular Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, protein kinase A (cAMP‐dependent protein kinase) activity is required for TCR‐dependent induction of TSAd expression 180 . Another potent activator of TSAd expression is a combination of phorbol myristate acetate and ionomycin (which bypasses immunoreceptor tyrosine‐based activation motif phosphorylation), both in T cells and NK cells 181 …”
Section: Tsad—an Adaptor With An Ambiguous Role In Cellular Signallingmentioning
confidence: 99%
“…Additionally, TSAd KO mice are more resistant to myeloma development than TSAd wild‐type mice in a myeloma‐specific TCR‐transgenic model 186 . Upon viral challenge, TSAd‐deficient mice displayed reduced clearance of murine cytomegalovirus in the spleen 181 . Murine SH2D2A −/− CD4 + T cells exhibited impaired polarization in the immunological synapse of multiple molecules involved in TCR signalling 190 .…”
Section: Tsad—an Adaptor With An Ambiguous Role In Cellular Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite TSAd being involved in TCR signalling, unchallenged Sh2d2a −/− mice display only minor alteration in overall immune phenotype 15 , 19 , 20 . TSAd may influence specific NK cell immune responses, since Sh2d2a −/− mice displayed reduced clearance of a mutant murine cytomegalovirus which does not activate the NK cell receptor Ly49H 21 . Recently, we found that TSAd affects CD4+ T cell-mediated rejection of experimental multiple myeloma 19 .…”
Section: Introductionmentioning
confidence: 99%
“…TSAd is rapidly induced at the mRNA and protein levels upon activation of T cells. [3][4][5][6] In addition, TSAd is expressed in natural killer (NK) cells 7,8 and in various epithelial cells. [9][10][11][12][13][14] Mice lacking TSAd display normal T cell differentiation, while the T cell receptor-induced proliferation of murine T cells is attenuated.…”
mentioning
confidence: 99%